Illusion and Reality in Mary Shelley’s Frankenstein (Raparin Journal of Humanities (RJH), 2023)
One of the fundamental keys to Mary Shelley’s Frankenstein is the division between illusion and reality. This study aims to demonstrate these two notions and how they function in the novel.  Most of the events which take place in Marry Shelley’s Frankenstein are related to illusion and reality. The characters are planning for a specific result and the structure of their plans seems to be something, but in reality, their plans become something different as they are based on illusions. Although this notion is mostly related to the protagonist of the novel, Victor Frankenstein and his creature, the Monster, it has reflected in the perception of other characters as well, like Robert Walton’s journey to North Pole, people’s concern over the Monster, the Monster’s perception to DeLacey family, the readers' perception of Alphonse Family and Justine Moritz’s idea about her sins. The analysis of this study focuses on the illusion of these characters as they believe in their truth, a seeming reality, a fabricated truth and their incapability to distinguish reality from illusion which leads to their downfall because they refuse the reality of their lives.